Santri's Perception of Hermeneutic Principles in Teaching Al-Qur'an and Tafsir in Pesantren - Ulhaq, Muhammad Miftah; Ghina Fadlilah Sukmara; Irawan (Yayasan pendidikan dzurriyatul Quran, 2025)
This research discusses the santri's perception of the hermeneutic principle in teaching the Qur'an and tafsir at Pesantren Al-Hikmah. The main issue raised is how hermeneutics, as a modern interpretation approach, is accepted and understood by santri in a tradition-based pesantren education environment. This study aims to identify santri perceptions, explore the challenges of hermeneutics implementation, and analyse its relevance in the development of pesantren education. The research used a qualitative method with a case study approach. Data were collected through in-depth interviews, participatory observation, and document analysis. The research subjects were senior santri, ustaz, and pesantren managers. The results show that the santri's perception of hermeneutics is divided into two: a group that accepts this approach as a relevant innovation to understand the Qur'an contextually, and a group that is sceptical because they are worried about deviations from classical interpretation. In teaching, hermeneutics is used to address contemporary issues such as social and environmental justice, but its implementation faces challenges in the form of ideological resistance, limited literature, and faculty capacity. The discussion shows that hermeneutics can be a bridge between tradition and modernity in Qur'anic interpretation, provided it is applied with a systematic approach and respect for tradition. In conclusion, the integration of hermeneutics in pesantren education has the potential to broaden students' horizons and answer the challenges of globalisation. This research contributes to the development of Islamic education theory, especially in the integration of classical and modern tafsir methods, and becomes the basis for further research on the application of hermeneutics in pesantren.